Development of novel polymeric nanoagents and their potential in cancer diagnosis and therapy runing title: Polymeric nanoagents for cancer theranostics - Huang, Ge; Li, Qian; Li, Longyan; Wang, E. (Frontiers in Chemistry, 2022)
Cancer has been one of the leading factors of death around the world. Cancer patients usually have low 5-year survival rates and poor life quality requiring substantial improvement. In clinic, the presenting diagnostic strategies lack sensitivity with only a small proportion of patients can be accurately identified. For diagnosed patients, most of them are at the advanced stages thus being delayed to receive treatment. Therefore, it is eager to investigate and develop highly effective and accurate techniques for cancer early diagnosis and individualized therapy. Various nanoplatforms are emerging as imaging agents and drug carriers for cancer theranostics recently. Novel polymeric nanoagents, as a potent exemplar, have extraordinary merits, such as good stability, high biosafety and high drug loading efficacy, showing the great prospect for cancer early diagnosis and precise treatment. Herein, we review the recent advances in novel polymeric nanoagents and elucidate their synthesis procedures. We further introduce the applications of novel polymeric nanoagents in cancer diagnosis, treatment, and theranostics, as well as associated challenges and prospects in this field.